PERCUTANEOUS NEPHROLITOTOMY ON THE MANAGEMENT OF CALYX INFERIOR STONES - Tirtayasa, Pande Made Wisnu; Birowo, Ponco; Rasyid, Nur (Indonesian Urological Association, 2014)
Objectives: To compare the stone free rates of inferior calyceal stones with stone burden < 20 mm, 21-30 mm, and > 30 mm on post-percutaneous nephrolithotomy (PCNL) patients in Cipto Mangunkusumo Hospital. Material & method: The data was collected retrospectively from PCNL medical records in Cipto Mangunkusumo Hospital between January 2000 until May 2012. Patients were followed-up with plain abdominal radiography (BNO) or renal ultrasonography (USG). Stone free status was defined as no residual fragments on radiography or USG. Results: As many as 88 patients with inferior calyceal stones who underwent PCNL were included. Forty-three cases had stone burden < 20 mm, 34 cases with stone burden 21-30 mm, and 11 cases with stone burden > 30 mm. Overall, 81 (92%) cases were defined as stone free. On group < 20 mm, 21-30 mm, and > 30 mm; 41 (95%), 32 (94%), and 8 (73%) cases defined as stone free respectively (p = 0.485). Conclusion: PCNL is the primary modalityon the management of calyx inferior stones with high stone free rate. The stone free rate of these three groups showed no statistically significant difference.Keywords: Percutaneous nephrolithotomy, inferior calyx stone, stone free rate.